2019
DOI: 10.1016/j.dib.2019.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Datasets of microarray analysis to identify Gpr137b-dependent interleukin-4-responsive genes in the mouse macrophage cell line RAW264

Abstract: Macrophages are classified mainly into two subtypes, M1 and M2, which exhibit distinct phenotypes, based on their microenvironment. We have recently demonstrated that Gpr137b is abundantly expressed in RAW264 macrophages, “ Gpr137b is an orphan G-protein-coupled receptor associated with M2 macrophage polarization” (Islam et al., in press) [1]. Although recent studies have suggested that G-protein-coupled receptors (GPCRs) are associated with M1/M2 macrophage polari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Recent data reported that TGR5 is highly expressed in monocytes/macrophages (36,38,39), members of the mononuclear phagocyte system that circulate through the blood and extravasate into inflamed tissues. We performed immunohistochemistry and confirmed that TGR5 is principally localized in the macrophage infiltrate of murine colonic samples, while FXR is mainly found in the nuclei of enterocytes (in uninflamed tissue).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent data reported that TGR5 is highly expressed in monocytes/macrophages (36,38,39), members of the mononuclear phagocyte system that circulate through the blood and extravasate into inflamed tissues. We performed immunohistochemistry and confirmed that TGR5 is principally localized in the macrophage infiltrate of murine colonic samples, while FXR is mainly found in the nuclei of enterocytes (in uninflamed tissue).…”
Section: Discussionmentioning
confidence: 99%
“…Recent data reported that TGR5 is highly expressed in monocytes/macrophages (35,37,38), members of the mononuclear phagocyte system that circulate through the blood and extravasate à P < 0.05; Ãà P < 0.01. FXR ¼ farnesoid-X-receptor; PXR ¼ pregnane-X-receptor; TEER ¼ transepithelial electric resistance.…”
Section: Discussionmentioning
confidence: 99%